PEMBUATAN BRIKET DAUN DARI LIMBAH PENGOLAHAN MINYAK KAYU PUTIH - Djeni Hendra (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
The experimental study on briqueting from leaf waste of cayeput oil distillation prepared by using the hydraulic press proess is presented in this paper. The tapioca flour is used as adhesive with five different consentrations i.e. 1 per cent, 1.5 percent, 2 percent, 3 percent and 5 percent. The responses evaluated are the moisture content, ash content, volatile matter, density, crushing strength and calorific value. The result shows that moisture content ranges from 12,21- 12,86 percent, ash content from 8, 02 - 8,85 percent, volatile matter from 68, 08 - 69, 45 percent, density from 0,251 - 0,325 gr/cm3. crushing sfrength from 9,60 - 19,82 kg/cm2 and the calorific value from 4326,46 - 4473.05 cal /gr.